Mekanisme Penciptaan Uang dalam Lembaga Keuangan Syariah: Antara Prinsip Kehati-hatian dan Fungsi Intermediasi - Arnelia Putri Pratiwi; Gama Pratama; Saefullah Fatah (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2025)
This study analyzes the mechanism of money creation in Islamic financial institutions by examining its relationship with prudential principles and financial intermediation. The research is motivated by the growth of Indonesia’s Islamic capital market, which reached a capitalization of IDR 5,060 trillion in 2025, yet conceptual challenges remain regarding money creation in line with maqashid al-shariah. The study employs a Systematic Literature Review (SLR) using the PRISMA framework, reviewing 38 relevant academic articles. Findings indicate that money creation in Islamic finance occurs only through real-asset-based activities, differing from the conventional system that relies on credit expansion and interest. Intermediation functions are carried out through partnerships emphasizing fair risk and profit sharing, while the prudential principle ensures controlled monetary expansion. The study concludes that the integration of moral and economic dimensions establishes a fair, stable, and sustainable Islamic monetary paradigm and contributes conceptually to strengthening Islamic financial policy in Indonesia.